2022
DOI: 10.1088/1742-6596/2238/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Polarization and biomineralization of hydroxyapatite-barium titanate composites

Abstract: In the search of new materials for bone regeneration, the materials with piezoelectric properties look very promising. It has been reported that piezoelectric materials induce bone growth and enhance implant integration. Additionally, it has been found that bioactivity increases in negatively charge surfaces such as polarized BaTiO3 (BT) and polarized hydroxyapatite (HAp). Additionally, it is known that BaSO4 (BS) increases biocompatibility. Therefore, in this work, composites materials of 80BT/20BS (BTS) in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Thus, it was shown that the ε1 values decreased when increasing the applied frequency. Notably, at each frequency, the ε1 values significantly decreased with the increase in the HA content: at 100 Hz, the ε1 values corresponding to 10% HA-90% BTS composite samples decreased by ~40% with a 10% The ε 1 values for HA-BTS sintered composites were also measured by Uribe et al [220] in the frequency range of 100 Hz to 100 kHz. Thus, it was shown that the ε 1 values decreased when increasing the applied frequency.…”
Section: Dielectric Constantmentioning
confidence: 55%
See 1 more Smart Citation
“…Thus, it was shown that the ε1 values decreased when increasing the applied frequency. Notably, at each frequency, the ε1 values significantly decreased with the increase in the HA content: at 100 Hz, the ε1 values corresponding to 10% HA-90% BTS composite samples decreased by ~40% with a 10% The ε 1 values for HA-BTS sintered composites were also measured by Uribe et al [220] in the frequency range of 100 Hz to 100 kHz. Thus, it was shown that the ε 1 values decreased when increasing the applied frequency.…”
Section: Dielectric Constantmentioning
confidence: 55%
“…The ε1 values for HA-BTS sintered composites were also measured by Uribe et al [220] in the frequency range of 100 Hz to 100 kHz. Thus, it was shown that the ε1 values decreased when increasing the applied frequency.…”
Section: Dielectric Constantmentioning
confidence: 78%
“…A lack of calcium ions in nonstoichiometric HA can also cause this band to arise due to the stretching vibration caused by free OH groups of water molecules trapped in lattice vacancies of OH ions [37]. Overall, the non-sintered HA shows a band of OH − (3575 cm −1 ) stretching vibration, which gradually decreased in intensity with an increase in the sintering temperature and completely disappeared in the 5HA/95BT sintered nanocomposite with the lowest HA content [38].…”
Section: Phase Composition and Molecular Structure Of Shbncsmentioning
confidence: 98%
“…Nanostructured HA-coated titanium and stainless-steel wires also showed induced expression of bone formation and provided osteointegration [76]. The biomineralization process of HA in HA/BT nanocomposites is significantly enhanced by the addition of BT and enhanced in polarized materials [38]. The in vitro experimentation of 10%HA/90%BT ceramics with increased BT content in dynamic loading device stimulated growth of osteoblasts and allows boneinducing activity without cytotoxicity [41].…”
Section: In Vitro Cytocompatibility Assaysmentioning
confidence: 99%